Enhanced Lipid Production in Chlamydomonas reinhardtii Caused by Severe Iron Deficiency - Devadasu, Elsinraju; Subramanyam, Rajagopal (Frontiers in Plant Science, 2021)
Microalgae are used as a source of lipids for the production of biofuels. Most algae produce neutral lipids under stress conditions. Here, lipid accumulation by the unicellular alga Chlamydomonas reinhardtii was examined during cultivation under iron-limiting conditions. Severe iron stress caused the cells to accumulate a significant amount of lipid, specifically triacylglycerols (TAGs), by compromising the growth. Semi-quantitative measurements by fourier transform infrared (FTIR) spectroscopy showed an increase in both carbohydrate and lipid content in iron-stressed C. reinhardtii cells compared to control. Analysis by flow cytometry and thin layer chromatography confirmed that severe iron deficiency-induced triacylglycerol accumulation to four-folds higher than in iron-replete control cells . This accumulation of triacylglycerols was mostly degraded from chloroplast lipids accompanied by overexpression of diacylglycerol acyltransferase (DGAT2A) protein. Furthermore, liquid chromatography-mass spectrometry analysis demonstrated significantly enhanced levels of C16:0, C18:2 and C18:3 fatty acids. These results indicate that iron stress triggers the rapid accumulation of triacylglycerols in C. reinhardtii cells. The enhanced production of these lipids caused by the iron deficiency may contribute to the efficient production of algal biofuels if we escalate to the photobioreactor's growth conditions.